Web 2.0 software tools : practical application for SME / SMI (Table of contents and abstract only) - Tan, Jenice Siaw Fong (2007)
Web 2.0 is a term often applied to a perceived on going transition of the World Wide Web from a collection of websites that just published informatiom to a full-fledged oomputing platform serving web applications to end users or the enterpise - Eventually Web 2.0 services are expected to replace desktop computing applications for many purposes.